Warisan Arsitektur Islam-Melayu di Kabupaten Labuhanbatu: Analisis Semiotika Masjid Besar Panai - Situmorang, Muhammad Ridho; Tanjung, Muaz (Medan Resource Center, 2025)
Mosques in Indonesia are not only places of worship but also cultural artifacts that reflect the integration of Islamic values with local architectural traditions. The Panai Grand Mosque, located in Labuhan Bilik Village, Labuhan Batu Regency, represents a unique expression of Islamic-Malay architecture that warrants academic attention. This study aims to explore the architectural characteristics of the mosque and examine how its design aligns with Islamic aesthetics and local cultural values. Employing a qualitative research method, data were collected through direct observation at the site, in-depth interviews with the mosque's nazir (caretaker), and literature review using books, journals, and visual documentation. The findings reveal that the mosque’s structure exhibits key elements of traditional Malay architecture while incorporating Islamic ornamental principles. This architectural synthesis not only enhances the aesthetic and spiritual experience of worshippers but also represents the enduring identity of the local Muslim community. The study highlights the importance of preserving such architectural heritage as a form of cultural expression that reinforces religious values and local identity.